Evaluación de la producción, sanidad y calidad de frutilla bajo un manejo agroecológico en el periurbano de Córdoba - Meneguzzi, Natalia; Narmona, Luis; Forestello, Stella Maris; Hernández, Miguel; Arrascaeta, Ana (Sociedad Argentina de Agroecología, 2021)
Poster